Digital Storytelling Intervention on Prosocial Behavior Improvement among Early Childhood - Ifti Aisha; Dian Veronika Sakti Kaloeti (Psympathic: Jurnal Ilmiah Psikologi)
The prosocial behavior in childhood needs to develop because it is associated with favorable developmental outcomes in later hood. Digital storytelling is a method that assumed can help in encouraging and improving social behavior. It is combined digital media, including text, images, music and video. Digital storytelling can effectively improve prosocial behavior as opposed to the traditional storytelling approach. This study aims to examine and explore the effect of digital storytelling intervention methods on children’s prosocial behavior. The research subjects were 11 preschool children ranged from 5-7 years old. This study uses a randomized experiments research design with the program is carried out consecutively in five days, consists of 1 session each day before class begins. Measurement was done by using an observation checklist which developed from five aspects (sharing, cooperating, helping, donating, honesty) of prosocial behavior. Results of Friedman test showed that there was a significant difference of prosocial behavior in each session. This finding indicates that there are differences in the value of prosocial behavior in each session after the child gets a digital storytelling program.